2020
DOI: 10.1016/j.jaci.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severity and mortality in adult COVID-19 inpatients in Wuhan

Abstract: Background: In December 2019, the coronavirus disease 2019 (COVID-19) outbreak occurred in Wuhan. Data on the clinical characteristics and outcomes of patients with severe COVID-19 are limited. Objective: We sought to evaluate the severity on admission, complications, treatment, and outcomes of patients with COVID-19. Methods: Patients with COVID-19 admitted to Tongji Hospital from January 26, 2020, to February 5, 2020, were retrospectively enrolled and followed-up until March 3, 2020. Potential risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

212
2,007
37
114

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,044 publications
(2,370 citation statements)
references
References 24 publications
(28 reference statements)
212
2,007
37
114
Order By: Relevance
“…Our search for COVID-19, SARS and MERS identified 5120 citations. After removing duplicates, screening titles and abstracts, and reviewing full texts, we ultimately included 1 cohort study 8 including 84 patients with COVID-19 and ARDS, 5 cohort studies [19][20][21][22][23] including 679 patients with COVID-19 but without ARDS, 3 studies (2 cohort studies 24,25 and 1 RCT 26 ) including 7087 patients with SARS, and 2 cohort studies 27,28 including 623 patients with MERS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search for COVID-19, SARS and MERS identified 5120 citations. After removing duplicates, screening titles and abstracts, and reviewing full texts, we ultimately included 1 cohort study 8 including 84 patients with COVID-19 and ARDS, 5 cohort studies [19][20][21][22][23] including 679 patients with COVID-19 but without ARDS, 3 studies (2 cohort studies 24,25 and 1 RCT 26 ) including 7087 patients with SARS, and 2 cohort studies 27,28 including 623 patients with MERS.…”
Section: Resultsmentioning
confidence: 99%
“…Very low-quality evidence from 2 cohort studies 19,23 including 331 patients with severe COVID-19 raised the possibility that corticosteroids may increase mortality compared with no corticosteroids (HR 2.30, 95% CI 1.00 to 5.29, MD 11.9% more) (Table 3, Figure 2). One cohort study 20 reported an increase in the composite outcome of mortality or ICU admission with steroid use.…”
Section: Severe Covid-19: Direct Evidence From Observational Studiesmentioning
confidence: 99%
“…Instead, it is necessary to empower territorial medicine allowing general practitioners to go to the patients' home with proper personal protective equipment (PPE) to perform SARS-CoV-2 swab at home and identify and isolate positive subjects at an early stage. Individual isolation and early medical therapy may allow the prevention of severe pulmonary complications that require hospitalization and intensive care and limit the spread of the infection [11].…”
Section: First Lesson: Infection Containment and Early Diagnosismentioning
confidence: 99%
“…The binding receptor of SARS-CoV-2 has been identified in the angiotensin converting enzyme (ACE)-2 and a Th-1 cytokine storm (IL-6 and TNF-α) sustains the lung inflammation of COVID-19, thus it is not expected a direct protective effect of AIT. Speculatively, the predominant Th-2 immune response in allergic patients might be beneficial and counter the inflammation process induced by SARS-CoV-2 [6]. Conversely, the therapeutic weapons fighting a Th-2 response, including AIT, could work indirectly by contributing to restore an impaired broad antiviral response.…”
mentioning
confidence: 99%
“…J Investig Allergol Clin Immunol 2020; Vol. 30(6) © 2020 Esmon Publicidad doi: 10.18176/jiaci.0568 AIT for years has been predominantly administered subcutaneously (SCIT), with periodic injections in a continuous schedule along the year or clustered preseasonal approaches. SCIT is safe provided adequate precautions are taken in a supervised facility, with properly trained staff and equipment to immediately manage severe reactions.…”
mentioning
confidence: 99%